Ectopic multiple digit replantation salvage of hand torsion injury following anterolateral thigh perforator flap coverage - Longbiao Yu; Kushal Shah; Fanbin Meng; Shengxiang Wan; Yingfeng Xiao; Fei Yu; Zhegang Zhou (JPRAS Open, 2023)
Retrieval of four finger injury at proximal stump amputation with segmental injury along with soft tissue defect and impending compartment syndrome continues to be challenge for the surgeon. Immediate transplant considering temporary ectopic foster as a practical option in special case. We describe temporary ectopic finger implant for crush injury at Metacarpophalangeal (MCP level) with hand torsion along with forearm compartment was fostered to Dorsum of the foot. The torsion fingers was temporary fixed with mini external fixator for stabilization as salvage, ALT free flap was used to cover soft tissue defect of the hand. Replantation of survived figure was performed using the long pedicle to anatomical site without crushing the MCP joint to allow for later tendon transfer for finger. Satisfactory function regained with no foster site (foot) complication like pain or disability. The author validated ectopic foster for amputee as and procedure of choice for salvage of extremity under special circumstances.